Creating Community in Teacher Education Classes with Hogwarts-style "Houses". Issue 6 (2nd November 2019) - Gandy, S. Kay
Abstract: The author successfully implemented the "House" system in a university social studies methods class and reports on the positive results that ensued. Students reported a sense of unity, camaraderie, identity, and closeness that was missing in many of their other classes. The House assignments and competitions are described, as well as ideas for other ways to use the House system.